INTOLERANCE UNCERTAINTY AS A MODERATOR BETWEEN RELIGIUSITY AND PSYCHOLOGICAL WELL-BEING IN UNEMPLOYMENT - Muslim, Abdul Aziz (Journal of Education Research and Evaluation, 2021)
A positive attitude in an individual can be formed if he has good psychological well-being. A good form of psychological well-being can organize oneself according to predetermined goals. The unemployed have very low psychological well-being so that many psychological problems. Many studies have linked religiosity with psychological well-being, with the result that there is a positive correlation between religiosity and psychological well-being. This research aimed to know the influence of religiosity and psychological well-being defined by intolerance of uncertainty. This research subjects were 220 persons unemployed in Malang City; they were 74 men and 146 women. The data of this research was collected by using some instruments, such as Orientation Scale-Revised (ROS-R), Intolerance of Uncertainty Scale (IUS-12), and Psychology Well Being Scale (PWBS). The data analysis of this research used Moderated Regression Analysis (MRA). The result of this research indicated that there was correlation between religiosity and psychological well-being (Î² = 0,707, p = 0,000), in spite of the correlation is getting weak when it is mediated by intolerance of uncertainty (Î² = -0,045, p = 0,046).